Organizational aspects of improved irrigation management: an experiment in Dewahuwa Tank, Sri Lanka - Ekanayake, R.; Groenfeldt, D. (International Irrigation Management Institute, 1990)
This report is one of several IIMI publications addressing the issue of irrigation management to promote diversified crops during the dry season. As Sri Lanka approaches self-sufficiency in rice production, a target already achieved by some other countries in the region, there is little logic in growing rice using land and water resources which could support higher- value non-rice crops, using less water. Thus, one of the incentives in improving irrigation management is to find ways of stretching water further during the dry season in water-deficit systems, when rice is relatively more expensive to grow than during the wet season, and when other crops which can be grown only during the dry season (when there is less danger of water-logging) offer the farmer and the country a comparative advantage.